Immigration Flows and Regional Labor Market Dynamics - Gross, Dominique (IMF Working Papers; Working Paper, 1998)
The paper analyzes the ability of a regional labor market to absorb growing flows of immigrant workers with declining levels of skills during relatively high unemployment. The impact of the size of the flow and the skill characteristics of the immigrants are analyzed. It is found that immigration is positively related to unemployment in the short run but in the long run is negatively related. Also, a higher average skill level among immigrants makes them more effective in their job search in the short run. Finally, increasing the discrepancy between the skill distribution of immigrants and that of the existing workforce is desirable, as both types of labor appear to be complements in the short-run.